MAKING DRY NOODLES MADE FROM CASSAVA FLOUR (MANIHOT ESCULENTA CRANTZ) AND CASSAVA STARCH - Adnan Engelen; Rahmat A Rahman; Arif Murtaqi Akhmad Mutsyahidan (UPPM Politeknik Gorontalo, 2020)
This study aimed to determine the best formulation of dry noodle making from cassava flour and cassava starch and to see the physical and chemical properties of dry noodles. This study used a completely randomized design (CRD) and LSD test if there was a significant effect. The tests carried out included organoleptic tests, air content analysis, ash content analysis, color analysis and texture analysis. The results showed that the best formulation of dry noodles was a composition of 120 grams of cassava flour and 80 grams of cassava starch (M1) with a moisture content value of 9.81%, an ash content analysis of 8,7%, a color analysis of 22,1% and a texture analysis. 117,27% and had a savory taste, the aroma was not too strong and the color was a bit pale yellow.